Hasil Pembelajaran Teknik Dasar Tenis Meja: Forehand, Backhand dan Smash di Kalangan Siswa SMK Negeri 5 Medan - Mawardinur Mawardinur; Mutia Prahsiska; Muhammad Khairul Ryan (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2024)
Objectives: This study evaluates the skill levels of fundamental table tennis techniques and identifies influencing factors among SMK learners. Methods: A descriptive quantitative approach with survey methods was employed, involving 40 purposively selected SMK students (25 male, 15 female) and validated assessment criteria for data analysis through descriptive statistics. Results: Significant variation was found in the mastery of table tennis techniques, with forehand as the most mastered (60% in good/excellent), followed by smash (50%) and backhand (45%), indicating varied proficiency across techniques. Conclusion: The study highlights notable differences in mastery levels of table tennis techniques, suggesting implications for enhancing pedagogical approaches and improving training programs, especially for backhand skills.